Adaptive agroforestry—mitigating climate change impacts by farmers’ perception in different climate conditions in Iran - Ghanbari, Sajad; Jafari, Mostafa; Ghasemi, Javad; Eastin, Ivan L.; Álvarez-Álvarez, Pedro; Sasanifar, Samira; Azizi, Mohsen; Eskandari, Leila (Frontiers in Forests and Global Change, 2025)
IntroductionDeveloping countries are particularly vulnerable to climate change (CC), thereby impacting food production and altering the species composition to deliver essential services. Sustainable land-use systems, such as agroforestry, have emerged as adaptive solutions to climate change. Agroforestry, which integrates trees and shrubs with crops or livestock, offers multiple benefits, including enhanced production, improved soil and water conservation, and increased carbon sequestration. A study assessing the impact of CC on agroforestry was carried out in Iran, spanning across semi-arid, semi-humid, and humid climates.MethodsData were collected from 204 households using surveys to understand the socioeconomic characteristics, land use, and agroforestry.Results and discussionThe results indicated significant differences in farming experience and land holdings (p < 0.01) across regions. Agroforestry was more prevalent in semi-arid regions, with alley cropping being the most common practice. Farmers’ attitudes toward continuing agroforestry were positive, although there was a general lack of information about the practice. The primary sources of information were other farmers and extension experts. Species diversity in agroforestry varied by region, with apples, walnuts, and poplars being the most common in semi-arid regions, while species diversity was generally lower in humid regions. To mitigate the impacts of climate change, adaptation strategies, such as altering crop and tree species to those more resilient to climate change, have been employed. The farm size assigned for the agroforestry systems in the semi-arid region was 0.86 ha, which was higher than that assigned in other regions. Farmers in the semi-arid regions rely on a greater diversity of species to mitigate CC impacts than those in other regions. This approach enhances the sustainability of agroforestry by optimizing resource use and maintaining agricultural productivity.